LncRNA MEG8 sponging miR-181a-5p contributes to M1 macrophage polarization by regulating SHP2 expression in Henoch-Schonlein purpura rats. (1st January 2021) - Jiang, Mingyu; Dai, Jicheng; Yin, Mingying; Jiang, Chunming; Ren, Mingyong; Tian, Lin
Abstract: Background: Long noncoding RNAs (LncRNAs) are regulatory molecules that play important roles in various biological and pathological processes. Herein, we aimed to explore whether maternally expressed gene 8 (MEG8) promotes M1 macrophage polarization among Henoch-Schonlein purpura (HSP) rats, and to investigate the underlying mechanism. Methods: Relative mRNA expression of MEG8, miR-181a-5p and suppressor of SH2 domain-containing tyrosine phosphatase 2 (SHP2) were examined using quantitative reverse transcription polymerase chain reaction. Furthermore, expression of SHP2 and the Janus kinase 2/signal transducer and activator of transcription 3 (JAK2/STAT3) pathway-related proteins was identified using western blot. Luciferase activity assay was conducted to evaluate whether miR-181a-5p could bind to MEG8 or SHP2. The macrophage phenotype was determined using flow cytometry and enzyme-linked immunosorbent assay. Results: We observed macrophage polarization towards the M2 phenotype in the peripheral blood of HSP rats. Furthermore, MEG8 and SHP2 expression were down-regulated, while miR-181a-5p was up-regulated in monocyte-derived macrophages from the HSP rats compared to the control group. Furthermore, MEG8 functioned as a sponge for miR-181a-5p in order to facilitate SHP2 expression. Moreover, miR-181a-5p mimic and SHP2 knockdown significantly reversed the MEG8 overexpression-mediated suppression of JAK2/STAT3 signalling, and promotion of M1 polarization. Conclusions: The lncRNA MEG8 sponged miR-181a-5p, which contributes to M1 macrophage polarization by regulating SHP2 expression in HSP rats. Key Messages: LncRNA MEG8 downregulation and M2 polarization in Henoch Schonlein purpura rats. MEG8 upregulation enhances M1 polarization and suppresses JAK2/STAT3 pathway. MEG8 sponges miRNA-181a-5p to regulate SHP2 expression. MiRNA-181a-5p upregulation reverses lncRNA MEG8-mediated enhancement of M1 polarization and inhibition of JAK2/STAT3 pathway. SHP2 downregulation reverses lncRNA MEG8-mediated enhancement of M1 polarization and inhibition of JAK2/STAT3 pathway.